$^{83m}$Kr calibration of the 2013 LUX dark matter search - LUX collaboration (93 authors) (2017)
LUX was the first dark matter experiment to use a Kr83m calibration source. In this paper, we describe the source preparation and injection. We also present several Kr83m calibration applications in the context of the 2013 LUX exposure, including the measurement of temporal and spatial variation in scintillation and charge signal amplitudes, and several methods to understand the electric field within the time projection chamber.